Pain coping strategies and their association with quality of life in people with Parkinson's disease: A cross-sectional study. - Tino Prell (Public Library of Science (PLoS), 2021)
Objective To develop multidimensional approaches for pain management, this study aimed to understand how PD patients cope with pain. Design Cross-sectional, cohort study. Setting Monocentric, inpatient, university hospital. Participants 52 patients with Parkinson's disease (without dementia) analysed. Primary and secondary outcome measures Motor function, nonmotor symptoms, health-related quality of life (QoL), and the Coping Strategies Questionnaire were assessed. Elastic net regularization and multivariate analysis of variance (MANOVA) were used to study the association among coping, clinical parameters, and QoL. Results Most patients cope with pain through active cognitive (coping self-statements) and active behavioral strategies (increasing pain behaviors and increasing activity level). Active coping was associated with lower pain rating. Regarding QoL domains, active coping was associated with better physical functioning and better energy, whereas passive coping was associated with poorer emotional well-being. However, as demonstrated by MANOVA, the impact of coping factors (active and passive) on the Short Form 36 domains was negligible after correction for age, motor function, and depression. Conclusion Passive coping strategies are the most likely coping response of those with depressive symptoms, whereas active coping strategies are the most likely coping response to influence physical function. Although coping is associated with pain rating, the extent that pain coping responses can impact on QoL seems to be low.